Review of OFC 2022 Optical Networks and Communications Conference Hybrid (Virtual/In-Person) Conference: 6–10 March 2022, San Diego, CA. Issue 3 (4th July 2022) - Hodara, Henri; Mock, Patrick; Skaljo, Edvin
ABSTRACT: We review the latest developments in Fiber-optic Telecommunications and Networks presented at OFC 2022 and compare the progress accomplished since the previous year conference, OFC 2021. In particular, we note this year's emphasis on the application of Neural Networks (NN) as part of Artificial Intelligence (AI) and Machine Learning (ML), as well as continued research in quantum communications and key distribution. We also expect future conferences to include papers about optical variants of quantum computers, a field of great interest that can exploit many quantum systems, as well as papers on continuing developments in High-Speed Communications beyond 800 Gb/s, and increased use of coherent modulation and detection in Data Centers Interconnect, Cloud and Edge computing, the latter in support of 5 G Internet Of Things (IOT).